The factors in shaping credit risk of commercial acceptance bills in supply chain finance in the Chinese real estate industry - Hongwei, Zhu; Wisedsind, Noppawan; Naknok, Sakchai (Edelweiss Applied Science and Technology, 2025)
This study investigates the credit risk associated with Commercial Acceptance Bills (CABs) within the supply chain finance ecosystem of China's real estate industry. As CABs gain prominence in facilitating liquidity, especially for small- and medium-sized enterprises, concerns about their default risk, regulatory gaps, and cascading financial repercussions have grown. Adopting a qualitative research design, this study captures the lived experiences and expert insights of 15 finance and legal professionals directly engaged with CAB issuance and risk management. Through thematic analysis, key risk determinants were identified across internal, external, and reputational dimensions. Findings reveal that poor liquidity management, high leverage, and ineffective governance significantly elevate CAB default risks. Furthermore, policy volatility, market fluctuations, and regulatory opacity intensify these vulnerabilities. Organizational reputation, meanwhile, emerged as a vital intangible asset that mediates trust and financial credibility in CAB transactions. The study contributes to both theory and practice by proposing a multi-dimensional framework for CAB risk governance and calls for integrated strategies to enhance transparency, resilience, and financial discipline in supply chain finance.